Domotics in inclusion and health: Descriptive Study (Innovation & Development in Engineering and Applied Science, 2023)
The present research is a bibliographic, exploratory, descriptive, and documentary study of the main contributions of the home automation area for people with disabilities, including mental, physical or temporary therapy. The study selects 30 journal articles or review articles from the Scopus database of the main quartiles Q1, Q2, Q3, that meet the purpose of the study and respond to the research question, from a total of 228 articles (208 articles, 20 reviews) of the last 10 years and that have English language. Among the main results, 3 specific areas of interest of the scientific community are identified: Telemedicine, home automation, Artificial Intelligence, in studies of remote monitoring for medical assistance of the elderly, disabled people, medical centers, additionally for intelligent energy management, portable sensors, IT Smart House, stress management, emergency calls, alternative communication with brain-computer interfaces, education and innovation of algorithms. The purpose of this research is to provide a first approach to the scientific, academic and business community that initiates learning in this area, in order to provide a review of the most relevant contributions in this line of knowledge.
Keywords: Telecommunications; artificial intelligence (AI); domotics; telemedicine